Ceding ground as a strategic concession in fact-checking: Shifting practice to shift power. (August 2022) - Waller, Lisa; Brookes, Stephanie
This article looks beyond functionalist accounts to consider how fact-checking organisations and practitioners interact with traditional and alternative sites of media power: holding and negotiating that power in their own right while interfacing collaboratively and strategically with those working in adjacent fields. Interpreted through this theoretical prism, interviews and a content analysis reveal how RMIT ABC Fact Check used its CoronaCheck project to renegotiate and renew its position of authority, and master time, during a moment of intense disruption in the media environment due to the global pandemic. With critical insights from the data as a foundation, the article argues that making strategic concessions in practice – conceptualised here as 'ceding ground' – can open spaces for new approaches in fact-checking.